Soil mineralogy and chemical properties as a basis for establishing nutrient management strategies in volcanic soils of Mount Ceremai, West Java - S Sukarman; Padana Aperta Barus; Rachmat Abdul Gani (Journal of Degraded and Mining Lands Management, 2020)
Soil mineralogy and its effect on chemical properties of volcanic soils located in Mount Ceremai has not been studied thoroughly. The objective of the study was to assess soil mineralogy and chemical properties of volcanic soils derived from different types and ages as an integrated strategic consideration to establish nutrient management. Field research and laboratory analysis were carried out on four soil profiles derived from different parent materials, namely young lava (KM-01), young pyroclastic fall (KM-02), old lava (KM-03), and old pyroclastic fall (KM-04). Results showed that KM-04 soil had limited nutrient reserved mineral (NRM), while KM-01, KM-02, and, unexpectedly, KM-03 soil still contained high NRM. There were no apatite and K-bearing mineral found in all soils, so regular P and K fertilization were recommended. Clay composition in the surface layer of KM-01 soil was dominated by amorphous minerals, while other soils contained amorphous mineral, gibbsite, and halloysite. Although all soils contained NRM such as labradorite, augite, and hypersthene, all soils had low exchangeable cations. P retention is a serious problem for all soils, especially KM-03 which has the highest amount of allophane. Therefore, nutrient management should be focused on accelerating NRM weathering, increasing soil CEC, and improving P fertilization efficiency.